HUWE1 Causes an Immune Imbalance in Immune Thrombocytopenic Purpura by Reducing the Number and Function of Treg Cells Through the Ubiquitination Degradation of Ets-1 - Li, Jianqin; Xia, Yalin; Fan, Xiaoru; Wu, Xiaofang; Yang, Feiyun; Hu, Shaoyan; Wang, Zhaoyue (Frontiers in Cell and Developmental Biology, 2021)
Background: Immune thrombocytopenic purpura (ITP) is an autoimmune bleeding disorder and the decreased number and immunosuppressive dysfunction of Treg cells are key promoters of ITP. However, their mechanisms in ITP development have not been fully clarified. Methods: HUWE1 mRNA and protein levels in CD4+ T cells in peripheral blood from ITP patients were assessed by quantitative real-time PCR and Western blot. HUWE1 function in ITP was estimated using flow cytometry, enzyme-linked immunosorbent assay and immunosuppression assay. Besides, the HUWE1 mechanism in reducing the number and function of Treg cells in ITP was investigated by immunoprecipitation, cycloheximide-chase assay, ubiquitin experiment and immunofluorescence assay. Results: HUWE1 expression was elevated in CD4+ T cells in peripheral blood from ITP patients and HUWE1 mRNA level was negatively correlated with platelet counts and Treg cell percentage. Moreover, the interference with HUWE1 increased the number of Treg cells and enhanced its immunosuppressive function, and the HUWE1 overexpression produced the opposite results. For the exploration of mechanism, HUWE1 interacted with E26 transformation-specific-1 (Ets-1) and this binding was dependent on the negative regulation of the phosphorylation level of Ets-1 (Thr38) and HUWE1 facilitated the ubiquitin degradation of Ets-1 protein to restrain Treg cell differentiation and weaken their immunosuppressive functions. The in vivo assay confirmed that the HUWE1 inhibitor alleviated ITP in mice. Conclusion: HUWE1 induced the immune imbalance in ITP by decreasing the number and weakening the function of Treg cells through the ubiquitination degradation of Ets-1.